On Application of Discrete Logarithms in Information - Hiding and Knapsack Problem with New Properties of Sk-Sets - Rizak AI-Rammahi, A.M.H (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Discrete logarithms are applied in many cryptographic problems . For instance , in public key . and for construction of sets with disti nct sums of k-clcments. The purpose o r this paper is to modify the method ol’ informationl1Â·iding using discrete logarithms , introduce new properties of St - sets , uscdthe direct product of groups to construct cyclic group and finally, present modified method for knapsack problem using each of discrere logarithms and S,-sets.